ANALISIS DERAJAT DESENTRALISASI FISKAL KABUPATEN SUMBAWA BARAT - Subhan Purwadinata; Deli Susmawati; Novi Kadewi Sumbawati (Pusat Riset dan Publikasi, 2022)
The purpose of this study was to determine the degree of fiscal decentralization in West Sumbawa Regency. This research is a descriptive research that aims to examine descriptively the degree of decentralization fiscal (DDF) of West Sumbawa Regency in 2015-2021. The type of data used is quantitative data in the form of regional original income (PAD), tax and non-tax profit sharing (BHPBP), and total regional income (TPD) of the West Sumbawa Regency for 2020-2021 obtained from documents and archives of the West Sumbawa Regency Regional Government Financial Statements which has been published online by the Central Bureau of Statistics (BPS) of West Sumbawa Regency. To find out the degree of fiscal decentralization of West Sumbawa Regency, it is calculated by the administrative independence ratio, namely the ratio of PAD to TPD ratio and the ratio of BHPBP to TPD ratio. The results of this study indicate that the average value of the DDF of West Sumbawa Regency in 2015-2021 based on the ratio of PAD to TPD ratio is in the very less category. The very low degree of fiscal decentralization of the PAD component shows that the ability of West Sumbawa Regency to implement fiscal decentralization is still very low. Meanwhile, the average value of the DDF for West Sumbawa Regency in 2015-2021 based on the ratio of BHPBP to TPD ratio is in the sufficient category. The sufficient DDF from the BHPBP component shows that West Sumbawa Regency has sufficient capacity to carry out fiscal decentralization.